المرأة والرجل الفروق الجنسية وصراع الأدوار (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2019)
تسجل العلاقة بين الرجل والمرأة أهمية خاصة في مسار التاريخ الإنساني. لقد سجلت هذه العلاقة الكثير من الأساطير المتنوعة حول جدل العلاقة بين الذكورة والأنوثة، وشكلت هذه العلاقة أيضاً مرآة ينعكس فيها تطور الإنسانية في مرحلة تاريخية. وتتحدد هذه العلاقة في صيغة جدلية تنطوي على مفهوم الصراع بين الرجل والمرأة حيناً والتوازن أحياناً أخرى. 1-     يسهم البحث في التعرف على علاقة المرأة بالرجل. 2-     ويتعرض إلى منشأ أصل الفروق الجنسية. 3-     ويتناول أهمية العمل بالنسبة للرجل والمرأة 4-     كما يعرض البحث بعض التوصيات حول أهمية التعاون بين الجنسين. Male- Female interaction plays an important role in the course of human history. Many myths and legends have been weaved around the dialectic of the relationship between femininity and masculinity. This relationship is a mirror that reflects humanity’s own progress during any given historical period. Male- female interaction is defined through a dialectical formula that at times encapsulates the concept of conflict between men and women, and at others relays the idea of balance between them. This research: 1-     Contributes to the understanding of the relationship between men and women. 2-     Explpres the origins of sexual differences. 3-     Deals with the importance of work for both men and women. 4-     Gives recommendation regarding the importance of cooperation between the sexes.